Punitiveness and atrocity: Why do some Filipinos support mass violence? - Deinla, Imelda B (Punishment & society, 2025)
Amidst the aftermath of the controversial war on drugs during Duterte's presidency in the Philippines, this study seeks to understand characteristics of Filipino punitiveness. The institutionalization of state violence, historical context of authoritarian rule, and societal acceptance of extreme measures prompt an examination of public attitudes toward crime, punishment, and violence in the Philippines. This study used survey data on Filipino respondents and identified five distinct punitiveness clusters using latent class analysis. This study employed Kruskal–Wallis (KW) tests and chi-squared tests to explore factors associated with differences in cluster characteristics. The analysis found that the extremely punitive group exhibited significantly higher levels of satisfaction with President Marcos Jr., a strong preference for authoritarian detachment, and lower trust in institutions compared to the other clusters. They support harsher penal policies including informal or extralegal methods such as torture, social cleansing, and use of violence to attain social progress. This study confirms the convergence of punitiveness and penal populism, where highly punitive citizens endorse strong leaders and extralegal measures that result in atrocities.